Contribution to the Anatomical Study of Urinary System in Pigs - Arenas, Fausto; Rincón , Josimar; Álvarez , Juan Camilo; Gómez , Fábian Alejandro; Cortés , Luz Stella (Spei Domus, 2015)
Introduction: There are few studies and research regarding the external and internal characterization of porcine kidney unlike other species. The purpose of this study was to establish the similarities for each type of anatomical pattern in the internal and external structures of the kidney and the renal secretion system of the species. Materials and Methods: The variables were analyzed from 60 renal blocks by injecting these with polyester resin, from animals destined for human consumption ethically obtained from the beneficiation plant Vijagual city of Bucaramanga. Result: External Morphometry for both kidneys, have a length of 120mm, the width of 27.3 mm. The renal arteries showed 3 different branching patterns (pattern I: 96.7%; pattern II: 1.7%; Pattern III: 1.6%). A third subpattern (Ic) in group I was found in 9.4% of samples. The distribution of the tributary veins present pattern type I (81%) and the pattern II (20%). Pattern III was not demonstrated in any of the examined samples. The caliber of the ureters averaged 6.9mm; the width of the renal pelvis was 12.2mm. The distribution patterns of the chalices were divided into two groups (A: 30% B 70%). Each pattern presented a subdivision in AI, AII, BI, and BII. Conclusions: The distribution patterns of renal structures found in this study are similar to those reported in previous studies, besides the contribution of an arterial pattern (Ic) was evidenced by this research.